Monitoring codling moth (Lepidoptera: Tortricidae) in orchards treated with pear ester and sex pheromone combo dispensers. (19th March 2012) - Knight, A.; Light, D.; Chebny, V.
Abstract Monitoring codling moth, Cydia pomonella (L.), with its sex pheromone (E, E)‐8, 10‐dodecadien‐1‐ol (codlemone) alone or in combination with plant volatiles (PH‐plant volatile lures) with and without the addition of an acetic acid (AA) lure was compared in apple and walnut orchards treated with PVC Cidetrak® dispensers (CM‐DA Combo) loaded with 60 mg pear ester, ethyl (E, Z)‐2, 4‐decadienoate (PE) and 185 mg codlemone. Lures were also evaluated in untreated apple and walnut orchards and apple orchards treated with Cidetrak® dispensers (CM) loaded with 120 mg codlemone. Traps with codlemone lures caught more moths than PE plus AA but similar numbers as traps with the PH‐PE lure in untreated apple and walnut orchards. The PH‐PE outperformed codlemone lures in apple orchards treated with CM dispensers. Codlemone outperformed PH‐PE lures in apple but not in walnut orchards treated mid‐season with CM‐DA Combo dispensers. Combining AA with PE significantly increased moth catch and together they performed similarly to the PH‐PE lure in all dispenser treatments in apple orchards. However, adding AA with the PH‐PE lure did not increase moth catches. The addition of AA to any of the lures tested except codlemone alone significantly increased the catch of females. Adding AA to either PE or the PH‐PE lure created a similarly attractive lure in orchards treated with CM‐DA Combo dispensers. Combining (E)‐4, 8‐dimethyl‐1, 3, 7‐nonatriene (DMNT) with codlemone in a combinational lure plus AA performed as well as any lure tested in apple orchards treated with CM‐DA Combo dispensers. Combinational lures loaded with either (E, E)‐farnesol, (E)‐β‐farnesene or DMNT performed significantly better than the PH‐PE lure in apple orchards treated with CM‐DA Combo dispensers only in the first generation. Both PH‐DMNT and PH‐farnesol lures were comparable to PH‐PE, except that the PH‐farnesol lure was less attractive to female moths.